ANALISIS PENGETAHUAN DAN BUDAYA IBU HAMIL TENTANG MANFAAT BERSALIN DI FASILITAS KESEHATAN - Merry Wijaya; Eka Marliana Putri; Ari Indra Susanti (Jurnal BIMTAS: Jurnal Kebidanan Umtas, 2018)
Introduction: Giving birth in a health facility is one of the efforts to make the complication in mothers during giving birth be well resolved. For the reduce morbidity and mortality maternal and neonatal, knowledge and culture of pregnant mothers has a major influence on it. The objective of this research was to know the description of the knowledge and culture of pregnant mothers about the benefit of giving birth at health service facility, this study was conducted inCommunity Health Center of Soreang years 2016. Methods: The method used in this research was descriptive method with cross-sectional design; the population in this research was all pregnant mothers,the samples was 80. The sampling used accidental sampling. The data were obtained by using primary data through questionnaires, and analyzed through univariate analysis.. Results: From the research result, it was obtained that the pregnant mothers with the characteristic age from 20 to 35 (16.2%), multigravida (13.8%), mothers whose education was senior high school level had good education (8.8%) had insufficient knowledge about the benefit of giving birth in the health service facility. Viewed from the influence of culture, pregnant mothers aged from 20 to 35 and multigravida pregnant mothers (21.2%) were influenced, while based on education (16.2%) pregnant mothers whose education was elementary school were those who were influenced by the culture regarding giving birth aid done at home by parajis (traditional midwives). Conclusion: The conclusion of the research, show that there are still pregnant women who have less knowledge about maternity benefits in health care facilities and there is still the cultural influence of pregnant women affect the mother to do home delivery assistance by paraji.